What are the complications of oral lipectomies? (Research, Society and Development, 2022)
Oral Lipectomy is a medical-dental procedure that aims to correct the volume of the adipose body of the cheek that is somehow generating unfavorable clinical implications for the stomatognathic system, being for facial aesthetic reasons, cause of trauma to the judgmental mucosa, occurrence of traumatic herniation. fat content into the oral cavity, or as a result of pathologies such as lipomas. Thus, this surgical procedure can be performed aiming at removing part of the fat content in the region indicated for the surgical procedure. However, in many cases this procedure can be accompanied by intraoperative complications such as hemorrhages or trauma to the parotid gland duct or nervous structures; as well as, postoperative complications such as: edema, trismus, emphysema, seroma, hematoma and infections may occur. Thus, the surgeon must be familiar with the surgical technique used and these procedures must be performed and followed with extreme caution to minimize possible complications and optimize their treatments.